'Crying out for help': containing primitive anxieties. From infant observation to under-5's brief therapeutic intervention. Issue 1 (3rd May 2020) - Vassiliki, Vassilopoulou; Maria, Tselika
ABSTRACT: This paper describes a brief under 5's intervention with a family who referred themselves to a hospital early intervention service. Material from the full piece of clinical work with the family is presented and discussed. The second session is presented in detail to give a sense of the distinctive features of the brief intervention for under-5's. The whole family was invited to attend, and the work was shared by two psychotherapists trained in the under 5s model of brief work. The significance of psychoanalytic infant observation in this type of intervention is highlighted. Infant observation enables the therapists to gather detailed impressions and thoughts to make meaning and to connect verbal and non-verbal communication between children, parents and therapists. The end-result is the creation of a transitional space, in which differentiation, creative thinking and change can take place.